bahasa inggris - Mika Tanti Nurwati; Suparni Suparni (Universitas Sarjanawiyata Tamansiswa, 2023)
Yogya Kembali Monument is one of the tourist attractions in which there are relics of the struggle for Indonesian independence in reclaiming the Special Region of Yogyakarta. In terms of form, if analyzed in depth, there is a connection with mathematical concepts. This study aims to explore mathematical concepts (ethnomathematics) in the Yogya Kembali Monument. The type of research used in this study is exploratory research with an ethnographic approach. Data collection techniques are done through observation, documentation, and literature studies. This study aims to explore the collection of objects contained in the Yogya Kembali Monument, which can then be used as a source of learning media in teaching mathematical concepts to students. This research resulted in the discovery of mathematical concepts in the Yogya Kembali Monument, generally in the form of Build Flat and Build Space. These results can be implemented into mathematics learning and an effort to increase the love of local culture through ethnomathematics-based learning.